1996
DOI: 10.1111/j.1432-1033.1996.0205n.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Individual Domains in Platelet Glycoprotein IIbIIIa

Abstract: Thermal denaturation of platelet glycoprotein IIbIIIa (integrin aI&) was investigated by spectrofluorimetry and differential scanning calorimetry (DSC). Two forms of the protein were compared: active IIbIIIa, i.e., that fraction that binds to RGD-Sepharose, and inactive IIbIIIa, the non-binding fraction. At pH 8.5 in the presence of octyl glucoside and Ca2+ both forms exhibited a broad complex endotherm consisting of a well expressed low-temperature heat-absorption peak in the range of 40-65 "C followed by a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
0
7
2
Order By: Relevance
“…In fact, this new thermostable conformer displays increased helicity, as monitored by a deeper 222-nm trough in the circular dichroic spectrum of ␣ IIb ␤ 3 , and a blue-shifted intrinsic fluorescence emission spectrum. The direction of both changes is opposite to that we and others (29,31,50) have described for guanidinium denaturation of the ␣ IIb ␤ 3 integrin. Our observations are also consistent with those of Makogoneko et al (50) who reported that ␣ IIb ␤ 3 was stable in octyl glucoside up to at least 95°C, based on fluorescence emission and scanning calorimetry measurements.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…In fact, this new thermostable conformer displays increased helicity, as monitored by a deeper 222-nm trough in the circular dichroic spectrum of ␣ IIb ␤ 3 , and a blue-shifted intrinsic fluorescence emission spectrum. The direction of both changes is opposite to that we and others (29,31,50) have described for guanidinium denaturation of the ␣ IIb ␤ 3 integrin. Our observations are also consistent with those of Makogoneko et al (50) who reported that ␣ IIb ␤ 3 was stable in octyl glucoside up to at least 95°C, based on fluorescence emission and scanning calorimetry measurements.…”
Section: Discussioncontrasting
confidence: 98%
“…The direction of both changes is opposite to that we and others (29,31,50) have described for guanidinium denaturation of the ␣ IIb ␤ 3 integrin. Our observations are also consistent with those of Makogoneko et al (50) who reported that ␣ IIb ␤ 3 was stable in octyl glucoside up to at least 95°C, based on fluorescence emission and scanning calorimetry measurements. Combining this information with the temperature-induced changes in receptor quaternary structure observed here by dynamic light scattering, sedimentation velocity, sedimentation equilibrium, and electron microscopy, we propose that the ligand-free ␣ IIb ␤ 3 integrin undergoes conformational changes and forms aggregates at temperatures above 35°C.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…The second questionnaire was to determine whether patients had made their definitive decision. Health outcomes measured by the Hip Disability and Osteoarthritis Outcome Score (HOOS) and the Knee Injury and Osteoarthritis Outcome Score (KOOS)[ 12 , 13 ]. Both questionnaires include questions about patients’ symptoms, pain, activity limitations in daily life, sport, recreation and quality of life.…”
Section: Methodsmentioning
confidence: 99%